Highly selective vagotomy and gastrojejunostomy in the treatment of peptic ulcer induced gastric outlet obstruction - Radovanović, Nebojša; Simić, Aleksandar; Skrobić, Ognjan; Kotarac, Milutin; Ivanović, Nenad (Vojnosanitetski pregled, 2014)
Background/Aim. The incidence of peptic ulcer-induced gastric outlet obstruction is constantly declining. The aim of this study was to present our results in the treatment of gastric outlet obstruction with highly selective vagotomy and gastrojejunostomy. Methods. This retrospective clinical study included 13 patients with peptic ulcer – induced gastric outlet obstruction operated with higly selective vagotomy and gastrojejunostomy. A 3-year follow-up was conducted including clinical interview and upper gastrointestinal endoscopy on 1 and 3 years after the surgery. Results. The most common preoperative symptom was vomiting (in 92.3% of patients). The mean preoperative body mass index was 16.3 ± 3.1 kg/m2, with 9 patients classified preoperatively as underweight. There were no intraoperative complications, nor mortality. At a 3-year follow-up there was no ulcer recurrence. Delayed gastric emptying was present in 1, bile reflux in 2, and erosive gastritis in 1 patient. Two patients suffered from mild “dumping” syndrome. Conclusion. Higly selective vagotomy combined with gastrojejunostomy is a safe and easily feasible surgical solution of gastric outlet obstruction induced by peptic ulcer. Good functional results and low rate of complications can be expected at a long-term follow-up.
Keywords: peptic ulcer; pyloric stenosis; vagotomy; proximal gastric; digestive system surgical procedures; treatment outcome